Implementation of Predictive Policing by Bhabinkamtibmas of Pemalang Police to Prevent Burglary in Order to Achieve Precision Police - Mitun, Aldian (Advances in Police Science Research Journal, 2024)
This research is motivated by the increasing cases of burglary that occur in the jurisdiction of the Pemalang Police. It was found that people who were afraid to report crimes that happened to them to the police (fear of crime) showed that Bhabinkamtibmas actions had not implemented predictive policing according to the direction of the Chief of Police. The purpose of the research was carried out to describe the implementation of predictive policing by the Bhabinkamtibmas Pemalang Police to prevent crimes by weighting within the framework of the Indonesian National Police with precision. The theory used in this research is George R. Terry's management theory and Program Implementation theory by Michele O Jones. The concepts used are the concept of Predictive Policing, the Concept of Bhabinkamtibmas, the Burglary Concept, the Precision Police Concept. The research method used is qualitative, with the type of document study research. The research location is in the jurisdiction of the Pemalang Police. Primary data sources were obtained using interviews, observation, and document studies. To test the validity using source and technique triangulation. Data analysis based on qualitative data analysis. The results of the study show that the implementation of predictive policing by Bhabinkamtibmas in activities carried out to prevent theft crimes by weighting in the jurisdiction of the Pemalang Police has not been carried out properly as evidenced by the existence of people who experience fear of crime. The activities carried out by the Bhabinkamtibmas Polsek Pemalang are not in accordance with Perkap Number 7 of 2021. In conclusion, the implementation of predictive polishing has not been carried out properly by utilizing existing applications. The activities carried out by Bhabinkamtibmas have not been on target. So that the problem-solving steps are expected to provide changes to the implementation of the Bhabinkamtibmas Predictive Policing of the Pemalang Police.